Iron metabolism patterns in non-anemic patients with myasthenia gravis: A cross-sectional and follow-up study - Li, Ke; Hou, Li'an; Tan, Ying; Huang, Yangyu; Shi, Jiayu; Han, Jianhua; Yan, Jingwen; Guan, Yuzhou (Frontiers in Neurology, 2022)
Background and purpose: Few published studies explored iron metabolism in myasthenia gravis (MG) and factors associated with it. This study aimed to compare iron metabolism patterns between MG patients and healthy individuals as well as between the same group of patients before and after immunotherapy, and to identify predictors for iron metabolism disorders in MG. Materials and Methods: One hundred and five patients and healthy individuals were included at baseline, after which paired parametric and non-parametric tests were adopted to compare their iron metabolism patterns, and multivariate binary logistic regression was used to identify predictors for iron metabolism disorders. MG patients were then followed-up for (12 ± 3) months to explore alterations in their iron metabolism patterns using paired tests. Results: Non-anemic immunotherapy-naïve MG patients had significantly lower serum iron (SI) and transferrin saturation (TS) concentrations compared with healthy individuals. Premenopausal female was significantly associated with SI < 65 μg/dL and iron deficiency in these patients. Iron metabolism parameters did not alter significantly after receiving immunotherapy for around 12 months in MG patients. Conclusions: Iron inadequacy was present in MG patients, particularly premenopausal female ones, and would hardly improve after immunotherapy. Given the essential role of iron in human body, it should be given more attention in MG patients.